EKSPERIMENTASI MODEL PEMBELAJARAN kOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) PADA MATERI POKOK TRIGONOMETRI DITINJAU DARI KECERDASAN EMOSIONAL SISWA SMK DI KOTA MADIUN TAHUN PELAJARAN 2013/2014 - Eva Tri Wahyuni; Budiyono Budiyono; Imam Sujadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aims of the research were to find out: (1) which produces better mathematics learning achievement among cooperative learning model Numbered Heads Together (NHT), Think Pair Share (TPS), or direct instruction model; (2) which have better learning achievement, students who have high emotional intelligence, medium, or low; (3) which gives a better learning achievement at each level of emotional intelligence, cooperative learning model Numbered Heads Together (NHT), Think Pair Share (TPS), or direct instruction model; (4) which have a better learning achievement at each learning model, students who have the emotional intelligence high, medium, or low. This research was a quasi-experimental research which designed a 3x3 factorial. The population of the research was all students at eleventh grade high school vocational and engineering technology group in Madiun city on academic year 2013/2014. The samples of the research were 264 respondents consisting of 87 students by using cooperative learning model Numbered Heads Together (NHT), 89 students by using cooperative learning model Think Pair Share (TPS), and 88 students by using direct instruction model. Analysis of the data used two-way analysis of variance. Based on the results of this research, it can be concluded: (1) the cooperative learning model NHT produces the same mathematics learning achievement as TPS, whereas NHT and TPS produce mathematics learning achievement better than the direct instruction model; (2) the students with high, medium and low emotional intelligence have the same learning achievement; (3) the emotional intelligence of each, NHT produces the same mathematics learning achievement as TPS, whereas NHT and TPS produce mathematics learning achievement better than the direct instruction; (4) the learning model of each, students with high, medium and low emotional intelligence have the same learning achievement. Keywords: NHT, TPS, Emotional Intelligence, Trigonometry.